The Responsibility Of The National Land Agency For The Issuance Of Certificate Breakdown Whose Parent Certificate Has Not Been Split - Altina Intan Nurfadila; Tjempaka Tjempaka (Jurnal Syntax Transformation, 2023)
Multiple certificates, namely a plot of land that has more than one certificate, causing legal uncertainty for holders of land rights which is highly undesirable in land registration in Indonesia. The purpose of this study, among other things, is to find out and analyze the responsibility of the National Land Agency when it was discovered that there were multiple certificates based on Decree Number: 177/Pdt.G/2022/PN Tjk. The research method uses a normative and empirical juridical approach. This case of multiple certificates can occur because the main certificate has not been mapped, so when an online check is carried out through an application it cannot be read, resulting in the re-creation of the certificate either partially or wholly on the same land by another party. If there are several certificates, the responsibility of the National Land Agency is to assist in mediation between certificate holders. If it cannot be resolved through mediation, the National Land Agency will help direct it to a settlement in the District Court or State Administrative Court because it is the State Administrative Court or District Court that can decide whether or not the certificate is cancelled.